Development of Static Fluid E-Module Contained with Local Wisdom of South Kalimantan - Muhamad Iqbal; Norsyifa Hasanah; Lutfiyanti Fitriah; Fahmi Yahya (Journal of Mathematics Science and Computer Education, 2023)
This research aimed to develop an electronic module on static fluid material that contained the local wisdom of South Kalimantan. This study used the ADDIE research and development design. The sample for this research was 62 students in class XI in one of the public schools in Banjarbaru, South Kalimantan. Data was collected with validation sheets and response questionnaires with a survey technique. The data was then analyzed using the Aiken formula and descriptive statistics. The results showed that the validity in terms of media was 0.92-1.00 and the validity in terms of material was 0.92-1.00. The average student response to the e-module is 4.40 in the very good category. Based on these results, it can be concluded that the developed e-module was valid and obtains a very good response, so it is suitable for use as a teaching material on static fluid material.